KONSEP BUSINESS PLAN UNTUK USAHA MIKRO KECIL MENENGAH - Hasni Hasni (Institut Agama Islam Negeri Bone, 2021)
The pandemic has had a significant impact on various aspects of human life worldwide, including in Indonesia. The business sector, especially micro, small and medium enterprises or MSME, has also been heavily impacted by the pandemic. As the most significant contributor to Gross Domestic Product, the government continues to strive so that MSME can bounce back. The rise of MSME will encourage improvement in the country's economic growth. Many programs are carried out by the government so that MSME can be active again. Still, these programs will not be helpful if entrepreneurs in the MSME sector do not know how to manage their business to survive uncertain external conditions. A business plan is one solution. Entrepreneurs who can make a good business plan will make the business run well. It can help formulate the right strategy to build a company that can survive in challenging conditions and become a sustainable business. The concept of a simple but effective business plan is explained in this article to help business actors in the MSME sector with implications for the government and the private sector to help MSME learn to develop their business plans.